Pengaruh Pasca Pandemi Covid Terhadap Sistem Kerja, Kinerja, Dan Motivasi Pada Karyawan Swasta di Jakarta - Ave, Tanty Dwi Regina (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
Abstract The 2019 Corona Virus Disease (Covid-19) pandemic is spreading throughout the region, including the work system and work motivation of private employees in Jakarta. Work systems and work motivation are the impacts that receive the most attention after COVID-19. The work system of employees or private employees in Jakarta has certainly experienced a decline due to the influence of outside or conditions in the local area. The performance of private employees after the pandemic is certainly experiencing a bit of confusion because they are used to working from home or working from home so this must be addressed immediately so that it doesn't fall further in again becomes depressed performance. Therefore, the transition of the work system from WFH to WFO must be planned immediately and started to be implemented. Through qualitative descriptive studies, this journal aims to reveals the significant impact post-pandemic has had on the work system, performance and work motivation of private employees in Jakarta to restore the work system due to Covid-19 pandemic. The existence of COVID-19 is the cause of changes to the work system, hence the strategy for restoring the work system is to rely on restarting to implement the WFO work system periodically so that private employees can adapt so that they only need to continue the work system and improve their performance and work motivation while in the office. The impact of post-COVID-19 must be handled immediately so that employees can carry out their activities in the office as usual. Keywords: Work System, Post COVID-19, Work Motivation, Performance